The grapevine kinome: annotation, classification and expression patterns in developmental processes and stress responses. Issue 1 (1st April 2018) - Zhu, Kaikai; Wang, Xiaolong; Liu, Jinyi; Tang, Jun; Cheng, Qunkang; Chen, Jin-Gui; Cheng, Zong-Ming (Max)
Abstract: Protein kinases (PKs) have evolved as the largest family of molecular switches that regulate protein activities associated with almost all essential cellular functions. Only a fraction of plant PKs, however, have been functionally characterized even in model plant species. In the present study, the entire grapevine kinome was identified and annotated using the most recent version of the grapevine genome. A total of 1168 PK-encoding genes were identified and classified into 20 groups and 121 families, with the RLK-Pelle group being the largest, with 872 members. The 1168 kinase genes were unevenly distributed over all 19 chromosomes, and both tandem and segmental duplications contributed to the expansion of the grapevine kinome, especially of the RLK-Pelle group. Ka/Ks values indicated that most of the tandem and segmental duplication events were under purifying selection. The grapevine kinome families exhibited different expression patterns during plant development and in response to various stress treatments, with many being coexpressed. The comprehensive annotation of grapevine kinase genes, their patterns of expression and coexpression, and the related information facilitate a more complete understanding of the roles of various grapevine kinases in growth and development, responses to abiotic stress, and evolutionary history. Genetics: Mapping molecular switches in grape: A comprehensive map of all the protein kinases (PKs) in grape is now available. PKs switch other proteins on or off by adding or removing a phosphate group. They regulate many cellular processes, coordinate plant growth, and trigger responses to various stresses. However, the number, relationships, and functions of PKs remain uncharacterized in most plants. Zong-Ming Cheng at Nanjing Agricultural University and the University of Tennessee mapped all the PKs in grape. Using the most up-to-date version of the genome, Cheng and coworkers identified over 1000 PKs, traced their evolutionary relationships, and identified which PKs are active in key growth phases. They also identified many PKs involved in response to stresses such as heat and drought. These results may help to improve stress tolerance in one of the world's most economically important fruits.